An Integrated Approach to Business Studies - Jewell, Bruce R. (Harlow : Longman, 2000)
This new edition mirrors the modular structure of the AS and A level specification requirements for business studies in one text. Exam practice is included, with advice and tips from a chief examiner.
Previous ed.: 1996.
Includes bibliographical references and index.
Keywords: Business; Industrial management; Business -- Problems, exercises, etc; Industrial management -- Problems, exercises, etc; Business and Management